Analisis Kelayakan Usahatani Hidroponik Di Kota Makassar - Awalia, Hardiyanti; Rukmana, Didi; Bakri, Rasyidah (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
Hydroponic farming is often cultivated in cities experiencing rapid population growth. Business feasibility analysis is carried out as an effort to determine the level of feasibility of running or continuing a hydroponic business by considering certain feasibility criteria. Thus, a business is said to be feasible if the profits obtained can cover all costs incurred, both direct and indirect costs. Business feasibility analysis is an important thing to do to avoid losses and for business development and continuity. This research analyzes the feasibility of hydroponic vegetable farming in Makassar City based on financial aspects, whether it is feasible or not and analyzes the feasibility of hydroponic vegetable farming in Makassar City based on non-financial aspects, whether it is feasible or not. Financial Aspects and Non-Financial Aspects to determine the feasibility of Hydroponic Farming in Makassar City. Based on the results of research on the feasibility of Hydroponic Farming in Makassar City from a Financial Aspect it is feasible to continue running and the feasibility of Hydroponic Farming in Makassar City from a Non-Financial Aspect is feasible to continue running.